Critical review of bariatric surgical outcomes in patients with Prader‐Willi syndrome and other hyperphagic disorders. Issue 5 (13th April 2022) - Gantz, Marie G.; Driscoll, Daniel J.; Miller, Jennifer L.; Duis, Jessica B.; Butler, Merlin G.; Gourash, Linda; Forster, Janice; Scheimann, Ann O.
Abstract: Objective: The aim of this study was to review bariatric procedure outcomes among patients with Prader‐Willi syndrome (PWS), melanocortin 4 receptor (MC4R) mutations, Bardet‐Biedl syndrome, and hypothalamic obesity. Methods: Systematic published literature review used the following search terms: "Prader‐Willi syndrome, " "Bardet‐Biedl syndrome, " "hyperphagia, " "bariatric surgery, " "MC4R"/"melanocortin 4 receptor", "hypothalamic obesity, " and "bariatric procedure." Information collected included demographics, genetics, anthropometry, procedure type, outcomes, and complications, with inclusion of case series and clinical reports given the rarity of the disorders. For PWS, postoperative weight‐change percentage and BMI up to 14 years following surgery were analyzed using general linear mixed models, with descriptive outcomes for other conditions. Results: A total of 54 publications were identified, with variable follow‐up periods for 202 patients (114 with PWS, 43 with MC4R mutations, 7 with Bardet‐Biedl syndrome, and 38 with hypothalamic obesity) among bariatric procedures. Weight loss of patients with PWS was greatest within 1 year of surgery, with weight‐change percentage not significantly different from 0 at 5 years. Long‐term results in other conditions were variable and featured suboptimal weight loss and increased reoperation risk. Conclusions: Bariatric procedures among hyperphagic individuals, including those with PWS, report variable results and outcomes. Benefits of bariatric surgery may be less durable in hyperphagic disorders in comparison with other patients with severe obesity.